Point-Merge 절차를 이용한 도착 스케줄링 및 조언 정보 생성 알고리즘 개발 - 홍성권; 김소윤; 전대근; 은연주; 오은미; Hong, Sungkweon; Kim, Soyeun; Jeon, Daekeun; Eun, Yeonju; Oh, Eun-Mi (한국항공운항학회지, 2017)
This paper proposes arrival scheduling and advisory generation algorithms which can be used in the terminal airspace with Point-Merge procedures. The proposed scheduling algorithm consists of two steps. In the first step, the algorithm computes aircraft schedules at the entrance of the Point-Merge sequencing legs based on First-Come First-Served(FCFS) strategy. Then, in the second step, optimal sequence and schedules of all aircraft at the runway are computed using Multi-Objective Dynamic Programming(MODP) method. Finally, the advisories that have to be provided to the air traffic controllers are generated. To demonstrate the proposed algorithms, the simulation was conducted based on Jeju International Airport environments.